KEBAHAGIAAN DALAM KESEDERHANAAN PADA CERPEN AS SA’ID HASAN KARYA KAMIL KAYLANI (KAJIAN STRUKTURALISME ROBERT STANTON) - Anna Miftahul Khasanah; Rohanda Rohanda (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This study aims to analyze the story facts character, plot, and setting in the short story “Sa’id Hasan” by Kamil Kaylani using the structuralist approach of Robert Stanton. Literature, as a reflection of life and a medium of cultural communication, is closely tied to the social environment in which it emerges. Short stories, as a popular literary form, offer concise yet meaningful narratives, making structural analysis essential to fully comprehend their messages. The structuralist approach holds that the meaning of a literary work lies not in isolated elements, but in the integration of its intrinsic components that form a coherent structure. This research focuses on three story facts outlined by Stanton’s theory: character, plot, and setting. The short story “Sa’id Hasan” tells the tale of a simple man named Hasan who appears cheerful but harbors deep sorrow over the loss of his family. The findings reveal that the story is rich with life values and effectively conveys the protagonist’s emotional depth through its well-organized structure. This research contributes theoretically to the development of structuralist literary studies, particularly in Arabic short stories, and offers practical benefits as a reference for academic studies in the field of Arabic Language and Literature.